2023
DOI: 10.1108/cfri-06-2022-0108
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic, economic policy uncertainty and the hedging role of cryptocurrencies: a global perspective

Muhammad Aftab,
Inzamam Ul Haq,
Mohamed Albaity

Abstract: PurposeThe COVID-19 pandemic has led to global economic policy uncertainty, which has increased the need to investigate ways to mitigate the uncertainty. This study aims to examine the potential of cryptocurrencies as a hedge and safe haven avenue against economic policy uncertainty.Design/methodology/approachThis study investigates the behavior of the five leading cryptocurrencies in relation to country-level and group-level economic policy uncertainty indices, as measured by the text-based method developed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Especially in times of crisis, our study period contains the Covid crisis. In this regard, Muhammad Aftab et al (2023) find that cryptocurrencies can serve as a safe haven during the COVID-19 pandemic. Thus, investors may benefit from using cryptocurrencies as a risk-management avenue during times of uncertainty.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in times of crisis, our study period contains the Covid crisis. In this regard, Muhammad Aftab et al (2023) find that cryptocurrencies can serve as a safe haven during the COVID-19 pandemic. Thus, investors may benefit from using cryptocurrencies as a risk-management avenue during times of uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…They noticed that Bitcoin’s returns and volatility increase during more uncertain times, just like gold. In addition, Muhammad Aftab et al (2023) find that cryptocurrencies can serve as a safe haven during the COVID-19 pandemic. As a result, investors may benefit from using cryptocurrencies as a risk-management avenue during times of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Youth who have a positive attitude towards investing but are concerned about laws and regulations may delay their investment decisions. Other researchers found that the cryptocurrency market is known for its high volatility (Aftab et al, 2023). Youth who have a positive attitude towards investing may be hesitant to enter a market that can experience significant price fluctuations.…”
Section: Goodness Of Fit Valuesmentioning
confidence: 99%